ГАДААДЫН ШУУД ХӨРӨНГӨ ОРУУЛАЛТ: МОНГОЛЫН УЛС ТӨРИЙН ОРЧИН - С.Базарпүрэв; Б.Нандин-Эрдэнэ (Politology, 2023)
Mongolia has transition to democratic society for twenty five years. This time, one of the work with related to liberation politic and economy. Such as, adoption of law "Foreign Invest" in 1993. This law in over twenty years, bring to significant in Mongolian politic and economy. Because, it is give lot of results of investments and new technologies in development of civil, entity and transaction of communication of marketplace. Since 2008, foreign direct investment grow up is related to activation of mining field. But latest two years, foreign direct investment decrease is to attract attention of politicians and researchers. I will be review of whether is the reason of FDI declined from Mongolian instability political environment or Chinese weakening economic growth slow condition is due to in the mining sector?